Zero Tillage or Reduced Tillage: The Key to Intensification of the Crop?Livestock System in Ethiopia - Aune, Jens B.; Asrat, Rahel; Teklehaimanot, Dereje Asefa; Bune, Balesh Tulema (International Food Policy Research Institute, 2006)
Numerous methods are available for increasing crop and livestock production in the Ethiopian highlands. Both national and international research institutes have developed technologies that are technically appropriate for these conditions. Examples of such technologies are the broad-bed maker for vertisols and cow traction (Zerbini, Woldu, and Shapiro 1999) and use of a single ox to pull the plow (Ouwerkerk 1990). However, farmers’ adoption of these technologies has been very limited, and farming is still characterized in most areas by low input use and limited use of improved technologies. Fertilizer application has increased in recent years because improved crop production packages have been introduced through the Ethiopian extension service. Fertilizer has been easy to introduce because it does not require fundamental changes in the farming system. These packages have been accompanied by supply of credit. However, introducing these packages to farmers has not been without problems, particularly in dryland areas where crop failures are common. Farmers are often forced to sell animals to repay their debt. Despite these problems, it must be recognized that fertilizers do have an important role to play if farming in Ethiopia is to progress.